CURRENTЕ ASPECTS OF TREATMENT OF ACUTE TONSILLOPHARYNGITIS IN CHILDREN - Yuldasheva G. G; Hikmatova Sh. U (Western European Studies, 2024)
The article presents diagnostic and therapeutic aspects of acute tonsillopharyngitis in children. The choice of treatment tactics for ATPh is a crucial task. On the one hand, this pathology is most often associated with excessive and unjustified prescribing of systemic antibacterial therapy, on the other hand, refusal of antibiotics can contribute to the development of serious complications. Timely etiological diagnosis and rational therapy of ATPh are an important link in the effectiveness of treatment of ATPh in children and prevention of antibiotic resistance of microorganisms
Keywords: resistance; antibiotic; therapy